Iodine-Mediated Annulation of S-Allylated α-Enolic Dithioesters: Rapid Access to 2-Alkylidene-1,3-dithiolanes at Room Temperature - Ramulu, B. Janaki; Chowdhury, Sushobhan; Nagaraju, Anugula; Koley, Suvajit; Anand, Namrata; Singh, Maya Shankar (Synthesis, 2015)
A new and operationally and user-simple domino protocol for the efficient synthesis of 2-alkylidene-1,3-dithiolanes has been developed via molecular iodine mediated iodocyclization of S-allylated α-enolic dithioesters at room temperature. The attractive features of this strategy include mild reaction conditions, short reaction time (5 min), high atom economy, high selectivity, easy purification, excellent yields, and wide substrate scope. Notably, many examples gave the exocyclic double bond of the 1,3-dithiolane with Z-configuration, while others gave E/Z mixtures; interconversion of the E- and Z-isomers was observed under acidic and thermal conditions.
Keywords: dithiolanes; cyclization; stereoselective; dithioesters; domino reaction